Effect of using butanol and octanol isomers on engine performance of steady state and cold start ability in different types of Diesel engines. (15th November 2016) - Zhang, Tankai; Jacobson, Lisa; Björkholtz, Cecilia; Munch, Karin; Denbratt, Ingemar
Highlights: Tested fuels with similar cetane number were conducted in production setting engines. Butanol and octanol isomers blends and Diesel offer coincident heat release profiles. Alcohols addition to Diesel in blends seems promote the combustion. The oxygen content of the blends sharply reduce particulate emissions. Tested blends have excellent cold start performance. Abstract: To reduce greenhouse gas (GHG) emissions and fossil fuel consumption, addition of renewable alcohols to Diesel fuel may offer a potential solution. However, use of such alcohol/Diesel blends in existing Diesel engines is not yet fully understood. In the present study, alcohol/Diesel blends were tested by examining engine performance and emissions in both a light duty (LD) engine and a heavy duty (HD) engine with settings typical of those used in production engines. In addition, cold start tests of the blends were performed in a multi-cylinder LD Diesel engine. Four different alcohols were selected to mix with Diesel, i.e. n -butanol, isobutanol, 2-ethylhexanol and n -octanol. These alcohols were blended separately with either hydrotreated vegetable oil (HVO) or di-tertiary-butyl peroxide (DTBP), acting as cetane number (CN) improvers, in Diesel fuel. The mixtures were prepared to have the same CN as Diesel fuel. The results indicated that with similar CN and the same engine settings, the alcohol/Diesel blends and Diesel fuel exhibited the same start of combustion and almost identical heat release processes. The blends generated slightly faster combustion and a higher indicated thermal efficiency than Diesel fuel under most of the tested conditions and in both engines. Diesel blends of n -butanol and 2-ethylhexanol showed good cold start performance in the multi-cylinder LD engine. Results regarding emissions demonstrated that the total particulate matter (PM) number was reduced when using alcohol/Diesel blends and the PM diameter seems to decrease as the amount of oxygen in the fuel was increased in the LD engine. It was concluded that alcohol/Diesel blends produce much less soot than Diesel fuel in both types of engine owing to the higher oxygen content in the blends but cause slightly increased NO formation.